Pengaruh Perilaku Konsumtif Masyarakat terhadap Penggunaan Kartu Kredit - Anni Zuhro Syafrida Hasibuan; Arnando Nasution; Rifandi Syahputra; Siti Aisah (LPPM IAI Nasional Laa Roiba Bogor, 2022)
This review plans to decide the destructive conduct of the local area towards the utilization of Visas. The technique utilized in this review is a quantitative strategy with a populace of charge card proprietors in the city of Medan. The consequences of this review demonstrate the utilization of Mastercards joined by unnecessary utilization by metropolitan networks, particularly in Medan. The intentions of metropolitan networks in the utilization of charge cards are adequacy and effectiveness as well as based on way of life and sign of societal position. Keywords: Consumptive, Credit Card